2022
DOI: 10.1212/wnl.0000000000200010
|View full text |Cite
|
Sign up to set email alerts
|

Lateropulsion Prevalence After Stroke

Abstract: Background and Objectives:Lateropulsion is a deficit of active body orientation with respect to gravity in the frontal plane, mostly observed after a stroke. It magnifies mobility limitations and so represents an emerging target in rehabilitation. Efforts to design specific interventional studies require some basic knowledge of epidemiology, which is insufficient today because many studies focused on a few severe forms in individuals called pushers. The objectives of this study were to bridge this gap.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In a meta-analysis of 22 studies including 5125 participants, the prevalence of lateropulsion (pusher syndrome) after stroke was 55.1% (95% CI, 35.9%–74.2%). 209 This decreased from 52.8% (95% CI, 40.7%–65%) in the acute phase to 37% (95% CI, 26.3%–47.7%) in the early subacute phase and 22.8% (95% CI, 0%–46.3%) in the late subacute phase.…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 95%
“…In a meta-analysis of 22 studies including 5125 participants, the prevalence of lateropulsion (pusher syndrome) after stroke was 55.1% (95% CI, 35.9%–74.2%). 209 This decreased from 52.8% (95% CI, 40.7%–65%) in the acute phase to 37% (95% CI, 26.3%–47.7%) in the early subacute phase and 22.8% (95% CI, 0%–46.3%) in the late subacute phase.…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 95%
“…When considering only the retrospective studies with a sample above 30 patients in order to avoid bias related to small samples (for similar procedures, see Dai et al, 2022 ), we observed that the prevalence of bodily self disturbances ranged from 0.1% to 27.3% (mean ± SD : 6.2% ± 7.3%; Table 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…When considering only the retrospective studies with a sample above 30 patients in order to avoid bias related to small samples (for similar procedures, see Dai et al, 2022), we observed that the prevalence of bodily self disturbances ranged from 0.1% to 27.3% (mean ± SD: 6.2% ± 7.3%; Table 2). Figure 4b shows that only EBS in the parietal lobe evoked disturbances of all five phenomenal components underlying the ordinary and healthy sense of the bodily self that were considered in the present systematic review (including all three subcategories of self location, agency, perceptual body image, first-person perspective, body ownership).…”
Section: Prevalence Of Bodily Self Disturbances During Ebsmentioning
confidence: 99%
“…Clinical data and brain images (computed tomography [CT] and magnetic resonance imaging [MRI]) of participants in one of the aforementioned studies were analyzed and met the following criteria: (1) ischemic or hemorrhagic stroke in the right hemisphere according to the definitions of the World Health Organization24; (2) hemiparesis based on the neurologic examination; and (3) no previous infarcts, bilateral lesions, or other substantial brain structural changes. Individuals with right-hemispheric lesions were selected as the right hemisphere is the most frequently affected hemisphere in imaging and prevalence studies reporting a prevalence of LP during the acute phase and over time 25…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with right-hemispheric lesions were selected as the right hemisphere is the most frequently affected hemisphere in imaging and prevalence studies reporting a prevalence of LP during the acute phase and over time. 25…”
Section: Participantsmentioning
confidence: 99%